PENGARUH KOMPENSASI DAN PENGAWASAN TERHADAP EFEKTIVITAS KERJA KARYAWAN PADA PT. TOYOTA AGUNG AUTOMALL PEKANBARU - Hardianto, Yudhi; ', Marzolina; ', Restu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study carried out on PT.Toyota Agung AutoMall Pekanbaru.Under the guldance of Marzolina,SE,.MM and Drs.Restu,.MSi..The research aims to examine the influence of Compensation and monitoring to the Employee Performance Effectivity. Object of this research were service advisor, foreman, and technical at Toyota Agung Automall Pekanbaru. There are seventy four questionnaires were sent, but only sixty three questionnaires are returned. That data are analyzed by multiple regression method. The variables were examined are influence of Compensation and monitoring to the Employee Performance Effectivity. The results of this research showed that Compensation has an effect to the Employee Performance Effectivity, monitoring has an effect to the Employee Performance Effectivity. And the result of this research showed that the compensation and monitoring have an effect to the employee performance effectivity. The results of this research also showed that coefficient determinant is 38,7%.Keywords : Effectivity, Compensation, and monitoring